The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1111/j.1467-8535.2007.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Students' response to traditional and computer‐assisted formative feedback: A comparative case study

Abstract: The national movement towards progress files, incorporating personal development planning and reflective learning, is supported by lecturers providing effective feedback to their students. Recent technological advances mean that higher education tutors are no longer obliged to return comments in the 'traditional' manner, by annotating students' work with red pen. This paper considers some of the options currently available for returning computer-assisted feedback, including the Electronic Feedback freeware. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 23 publications
7
97
0
3
Order By: Relevance
“…Using technology to publish feedback Sending tutors' comments electronically (Bloxham and Boyd 2007;Crossouard and Pryor 2009;Denton 2001aDenton , 2001bDenton , 2003Denton et al 2008;Gipps 2005;Irons 2008) is an effective and simple means of communicating formative feedback to students, and can enhance the way in which students receive and engage with feedback. This may be feedback on an individual or group piece of work, or feedback generic to an entire student cohort on a module.…”
Section: Resultsmentioning
confidence: 99%
“…Using technology to publish feedback Sending tutors' comments electronically (Bloxham and Boyd 2007;Crossouard and Pryor 2009;Denton 2001aDenton , 2001bDenton , 2003Denton et al 2008;Gipps 2005;Irons 2008) is an effective and simple means of communicating formative feedback to students, and can enhance the way in which students receive and engage with feedback. This may be feedback on an individual or group piece of work, or feedback generic to an entire student cohort on a module.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent research focused on students' feelings towards different feedback methods on written assignments and how this affects their performance (Birjandi & Tamjid, 2010). Studies reported positive attitudes towards visual and auditory assessment and findings showed that students perceived e-feedback as more valid and valuable than written feedback (Denton, Madden, Roberts, & Rowe, 2008;Crews & Wilkinson, 2010). Cunningham (2015) investigated 31 pre-medical students' perceptions and achievement on the feedback perceived on their writings.…”
Section: Related Studiesmentioning
confidence: 99%
“…Denton et al (2008) compared the reactions of students to handwritten and electronic feedback using Electronic Feedback software. Students rated the electronic feedback superior for "markscheme clarity, feedback legibility, information on deficient aspects, and identification of those parts of the work where the student did well", and the lecturers reported taking less time to mark when using the software.…”
Section: Students' Feedback Preferencesmentioning
confidence: 99%